(untitled) - Milner, Robin (Cambridge, 1999)
The π-calculus differs from other models of communicating behaviour mainly in its treatment of mobility. The movement of a piece of data inside a computer program is treated exactly the same as the transfer of a message - or indeed an entire computer program - across the internet. One can also describe networks which reconfigure themselves. The calculus is very simple but powerful; its most prominent ingredient is the notion of a name. Its theory has two important ingredients: the concept of behavioural (or observational) equivalence, and the use of a new theory of types to classify patterns of interactive behaviour. The internet, and its communication protocols, fall within the scope of the theory just as much as computer programs, data structures, algorithms and programming languages. This book is the first textbook on the subject; it has been long-awaited by professionals and will be welcomed by them, and their students.
Keywords: Mobile computing,Telecommunication systems,Pi-calculus,Hệ thống viễn thông; Mathematical models,Mathematical models,Mathematical models,Mô hình toán học